Filosofi Informasi Dalam Pemberdayaan Layanan Perpustakaan - Umar Falahul Alam (Pustakaloka, 2014)
Abstract:  The existence of the library indicates information services.  The  service  shows  two  interrelated  variables: the  provider  on  the  one  hand  and  consumers  on  the  other. Because of relation between service provider and customer satisfaction, then the service should be  increased  from time to time. Library services also needs to be improved. Increased library  services must  be  appropriated  by  it’s  responsibility  to support  education,  teaching,  research  and  community service. There is no doubt, that the library plays an important role in  the  process  of  education  and  teaching. The  frst  library becomes  an  intermediary  between  the  users  and  their information needs. Second, the library can be an information provider  on  one  side  and  can be  consulted  for  the users  in their academic activities. Third, the library can be a teacher who teaches the users the skills and strategies in managing, utilizing, and  creating  information. The  role of  the  library likes this, is named empowerment of library services